Grenada, OECS Fiscal Issues : Policies to Achieve Fiscal Sustainability and Improve Efficiency and Equity of Public Expenditures - World Bank (Washington, DC, 2013)
The report reviews Grenada public expenditures for the period 1995-02 and suggests policy recommendations to achieve fiscal sustainability, improve social service delivery, and reform social protection based on the economic situation of the country at the time. To restore rapid economic growth, ensure medium-term fiscal sustainability under the umbrella of the currency union and protect the social achievements realized in the past decades, the main challenges facing the Grenada government are to: (a) tighten fiscal policy, notably through reduction of capital expenditures and the realization of the fiscal savings expected from the public sector reform initiated in 1997 (b) increase the efficiency of public investments and public service delivery; (c) strengthen regulation and efficiency of public utilities and sea/air transport; (d) modernize the legal framework that oversees public sector employment; and (e) promote education and skills development to prepare the population, notably the poor, to take advantage of new opportunities in the global environment. The report is organized as follows: Chapter 1 discusses fiscal sustainability in Grenada and presents options for fiscal consolidation; Chapter 2 discusses the role of the business cycle in the design of fiscal policy by reviewing the cyclical components of the fiscal accounts; Chapter 3 discusses the budget management system in place and its effect on budgetary outcomes. Chapter 4 examines the Public Sector Investment Program (PSIP); Chapter 5 discusses public sector employment and compensation issues; Chapters 6 and 7 examine public expenditures and outcomes in the education and health sectors; and Chapter 8 discusses social protection programs. Since the completion of the report, Grenada has undertaken a number of important initiatives to address the fiscal challenges that the country faces, especially in the aftermath of Hurricanes Ivan and Emily. In particular, the authorities have developed a "burden-sharing" strategy to achieve fiscal sustainability. However in Grenada, as in all small states, faster implementation is hindered by limited institutional capacity.